Perhitungan Koreksi Refraksi dalam Penentuan Tinggi Matahari Pada Awal Waktu Salat Asar - Saputra, A. Zuhrudin Hadi; Khazin, A. Mufti (Azimuth: Journal of Islamic Astronomy, 2024)
This article is the result of research related to the Calculation of Refractive Correction in Determining the Height of the Sun at the Beginning of the Asar Prayer Time" This research is a Research and Development approach research, by producing a product in the form of a refractive calculation for the height of the Sun at the beginning of the Asar prayer time. The primary data source used is the article Impact of Atmospheric Refraction on Asr Time by Abdurrahman Ozlen, the book Mechanics of Celestial Bodies. The method of data collection in this study is documentation. The data analysis method used in this study is qualitative descriptive analysis, which is obtained from the results of the refractive correction calculation in determining the height of the Sun at the beginning of the Asr prayer time. The results of this study conclude. First, the calculation of the refractive correction in determining the height of the Sun at the beginning of the Asar prayer time is to calculate the angle of the Sun's height that appears at the time of the Sun reaches the culmination point, then calculate the height of the Sun visible at the beginning of the Asar time, calculate the height of the true Sun at the beginning of the Asar time which has been corrected by refraction, and finally is to calculate the entry of the beginning of the Asar prayer time